Approaches to assessing the tourist and recreational attractiveness of a territory on the example of the Dnipropetrovsk area (Economics and region, 2023)
There are significant differences between sectoral zoning and planning schemes for recreation and tourism development areas in Ukraine. The principles established in the implementation of sectoral recreation and tourism zoning are not always consistent with the normative legal acts regulating the spatial planning system. The available results of scientific and applied research testify to the significant recreational and tourist potential of our country, which is formed by all available natural, historical, cultural and socio-economic resources. The formation of recreational, tourist, resort and health complexes for the purpose of effective and rational use of nature is relevant in today's uncertain socio-economic conditions. During the research the following methods of scientific knowledge were used: theoretical generalisation, factor analysis, economic-mathematical modelling, graphical, analytical and statistical methods. A methodology is proposed for assessing the level of tourist and recreational attractiveness of a territory, based on the consideration of ten criteria, the interpretation of which is carried out according to the appropriate scale. The methodology is characterised by sufficient simplicity, economy, high information capacity and is based on open statistical data. It was found that the estimated level of tourist and recreational attractiveness of Dnipropetrovsk Area is average. This indicates insufficient use of the existing tourist and recreational potential. It is suggested that the branding of the region should be based on the concept of preservation of Cossack traditions, natural resource potential and sustainable development.
Keywords: tourist and recreational attractiveness; potential; tourist resources; infrastructure; attractions; assessment; ecotourism; birdwatching